Novel modular mixed-mode dryer for enhanced solar energy utilization in agricultural crop drying applications - Aydin, Devrim; Ezenwali, Shedrach E.; Alibar, Mohamed Y.; Chen, Xiangjie (Taylor & Francis Inc, 2021)
In this study, a novel modular solar dryer unit which is made up of corrugated plates and a glass glazing has been investigated. The developed dryer was integrated with a solar air heater and experimented in mixed-mode operation for crop drying in Northern Cyprus. Average drying rate and drying efficiencies for apple, banana, chili pepper, and grapes were found as 30.2, 82, 67.8, and 98 g/h and 38.1%, 43.84%, 40.03%, and 42.12%, respectively. Average temperatures across the dryer were also measured as 43 degrees C, 47 degrees C, 48 degrees C, and 44 degrees C for the same order of materials.
Keywords: Mixed-mode; solar dryer; modular and multi-layer; corrugated plate; thermodynamic analysis; experimental